L'évolution historique du statut juridique des langues au Canada - Deschênes, Jules (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
The legal status of the French and English languages in Canada has been a difficult question for the past two hundred years. In the following article, the Honorable Jules Deschênes traces the evolution of the two official languages. He points out that any given linguistic situation is a direct product of the concerned country's political decisions and adds that politics and culture do not necessarily go hand-in-hand. The author also stresses the fragility of legal action as a means of maintaining or eliminating a given language in a society.